Rice husk filled polystyrene : biodegradability study and influence of coupling agent on its mechanical properties - 236576 Heng, Chee Shin (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Bachelor of Chemical Engineering (Polymer)) - Universiti Teknologi Malaysia, 2006